Positive electrode material, secondary battery, and electronic device
By covering the surface of the lithium phosphate positive electrode material and doping nitrogen elements, the problem of insufficient rate discharge performance and cycling performance of existing materials in secondary batteries is solved, and higher conductivity and stability are achieved, improving the overall performance of the battery.
Patent Information
- Application Number
- CN202510099581.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
AI Technical Summary
The existing lithium phosphate positive electrode materials have problems in secondary batteries with slow ion diffusion rate and low electron conductivity, which affect the rate discharge performance and cycling performance.
By covering the carbon layer on the surface of the lithium phosphate positive electrode material and doping nitrogen elements into the carbon coating layer, the conductivity and stability of the material are improved, thereby improving the rate discharge performance and cycling performance of the secondary battery.
It has achieved the significant improvement of the rate discharge performance and cycling performance of the secondary battery while maintaining safety and environmental friendliness, and met the demand for high-performance positive electrode materials.
Smart Images

Figure BDA0005254125090000181 
Figure BDA0005254125090000191 
Figure BDA0005254125090000192
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and in particular to a positive electrode material, a secondary battery and an electronic device. Background Art
[0002] As people's demand for electronic products such as mobile phones, laptops, cameras, etc. increases year by year, secondary batteries play an increasingly important role as the power source of electronic products in our daily lives, thus driving the demand for improved secondary battery performance. Lithium phosphate materials are used as positive electrode materials, which have the characteristics of high safety, abundant raw materials and environmental friendliness, but they also have problems such as slow ion diffusion rate and low electronic conductivity, which affect the rate discharge performance of secondary batteries. Therefore, it is imperative to provide lithium phosphate positive electrode material secondary batteries with excellent rate discharge performance. Summary of the invention
[0003] The embodiments of the present application provide a positive electrode material, a secondary battery and an electronic device, which achieve better rate discharge performance while improving cycle performance.
[0004] In the first aspect, the embodiment of the present application provides a positive electrode material, including a core and a carbon coating layer, wherein the carbon coating layer covers at least a portion of the surface of the core; the core includes lithium phosphate, and the carbon coating layer includes nitrogen. Based on the total mass of the positive electrode material, the mass percentage of the carbon element is A%, 0.8≤A≤3; based on the total mass of the positive electrode material, the mass percentage of the nitrogen element is B%, 0.2≤B≤0.8.
[0005] Based on the positive electrode material of the embodiment of the present application, the inventors found that coating the surface of the polyanionic lithium phosphate material with a carbon layer can increase the conductivity of the material. On this basis, the carbon coating layer is further doped with nitrogen. Since nitrogen atoms have a slightly smaller atomic radius and greater electronegativity than carbon atoms, the addition of nitrogen into the graphite structure of the carbon nanomaterial will change the atomic and electronic structure of the matrix and increase its conductivity, thereby improving the rate discharge performance of the secondary battery and improving the cycle performance.
[0006] In some embodiments, the positive electrode material satisfies at least one of the following conditions: (1) 1.2≤A≤2.6; (2) 0.3≤B≤0.5. Based on the above embodiments, the present application can further improve the rate discharge performance of the secondary battery and improve the cycle performance by controlling the mass percentage of carbon in the positive electrode material and the mass percentage of nitrogen in the carbon coating layer within the above ranges.
[0007] In some embodiments, the form of the nitrogen element in the above-mentioned carbon coating layer includes at least one of pyridinic nitrogen, amino nitrogen, pyrrolic nitrogen, graphitic nitrogen or oxidized nitrogen; based on the total mass of the positive electrode material, the mass percentage of graphitic nitrogen is C%, 0.2≤C / B≤0.6. Based on the above embodiments, when the nitrogen element in the carbon coating layer on the surface of the positive electrode material exists in the form of pyridinic nitrogen, amino nitrogen, pyrrolic nitrogen, graphitic nitrogen or oxidized nitrogen, a delocalized conjugated system of sp2 hybridized carbon can be formed to improve the conductivity of the carbon coating layer; at the same time, the conjugated electrons of the nitrogen-doped carbon structure coordinate with the empty transition metal orbitals on the surface of the core lithium phosphate material, and the binding force is improved, which can improve the stability of the surface coated carbon layer, thereby further improving the rate discharge performance of the secondary battery and taking into account the improvement of the cycle performance.
[0008] In some embodiments, the chemical formula of the positive electrode material is LiMn a Fe 1-a PO 4 , 0≤a≤1. Based on the above embodiments, the positive electrode material of the present application includes the above lithium phosphate salt, which can further improve the rate discharge performance of the secondary battery and improve the cycle performance.
[0009] In some embodiments, the positive electrode material further includes an X element, and the X element includes at least one of magnesium, vanadium, titanium, niobium, tungsten, molybdenum, nickel or cobalt; based on the total mass of the positive electrode material, the mass content of the X element is x ppm, 500≤x≤5000. Based on the above embodiments, the lithium phosphate positive electrode material of the present application includes the above doping elements, and the mass percentage content is within the above range, which can further improve the rate discharge performance of the secondary battery and improve the cycle performance.
[0010] In some embodiments, the positive electrode material satisfies at least one of the following conditions: (1) the X element includes at least one of magnesium, vanadium, titanium or tungsten; (2) 2000≤x≤3500; (3) 5000≤x / a≤15000. Based on the above embodiments, the present application can further improve the rate discharge performance of the secondary battery and improve the cycle performance by controlling the type and content of each metal in the lithium phosphate salt within the above range.
[0011] In some embodiments, the ratio of the D / G peak of the carbon coating layer is N, 0.90≤N≤1.2; and / or, the thickness of the carbon coating layer is H nm, 1≤H≤10. Based on the above embodiments, the D / G value of the carbon coating layer on the surface of the lithium phosphate material in the present application is within the above range, indicating that the carbon coating layer has a relatively balanced degree of graphitization and defect; the thickness of the carbon coating layer is regulated within the above range to be a relatively suitable thickness, thereby improving the rate discharge performance of the secondary battery while taking into account the improvement of the cycle performance.
[0012] In some embodiments, the diameter of the positive electrode material is D nm, 50≤D≤500; and / or the specific surface area of the positive electrode material is S m 2 / g, 10≤S≤50. Based on the above embodiments, the diameter of the lithium phosphate salt material in the present application is within the above range, and the particle size of the material particles is at a relatively suitable level; the specific surface area of the lithium phosphate salt material is within the above range, and the material particles have a relatively balanced specific surface area coefficient, which can improve the rate discharge performance of the secondary battery while improving the cycle performance.
[0013] In a second aspect, an embodiment of the present application provides a secondary battery, including a positive electrode plate, the positive electrode plate including a positive electrode collector and a positive electrode material layer located on at least one surface of the positive electrode collector; the positive electrode material layer includes the above-mentioned positive electrode material.
[0014] In a third aspect, an embodiment of the present application provides an electronic device, which includes the secondary battery mentioned above. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.
[0016] A first aspect of an embodiment of the present application provides a secondary battery, including a positive electrode, a negative electrode, an electrolyte and a separator.
[0017] positive electrode
[0018] The positive electrode includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode material layer includes a positive electrode material.
[0019] The positive electrode material includes a core and a carbon coating layer, and the carbon coating layer covers at least a portion of the surface of the core. For example, the carbon coating layer can cover the entire outer surface of the core, or it can cover part of the outer surface of the core. The core includes lithium phosphate, and the carbon coating layer includes nitrogen. Based on the total mass of the positive electrode material, the mass percentage of the carbon element is A%, 0.8≤A≤3, and preferably 1.2≤A≤2.6. For example, the mass percentage of the carbon element in the positive electrode material can be 0.8, 1.1, 1.2, 1.4, 2.0, 2.3, 2.6, 2.9, 3, or a value within the range of any two of these values. Based on the total mass of the positive electrode material, the mass percentage of the nitrogen element is B%, 0.2≤B≤0.8, and preferably 0.3≤B≤0.5. For example, the mass percentage of the nitrogen element in the carbon coating layer can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.8, or a value within the range of any two of these values. Coating a carbon layer on the surface of a polyanionic lithium phosphate salt material and further doping the carbon coating layer with nitrogen can enhance the rate discharge performance of the secondary battery while also improving the cycle performance.
[0020] In some of the embodiments, the form of the nitrogen element in the above-mentioned carbon coating layer includes at least one of pyridinic nitrogen, amino nitrogen, pyrrolic nitrogen, graphitic nitrogen or oxidized nitrogen. In the present application, the nitrogen element in the carbon coating layer in the form of oxidized nitrogen refers to the oxidized nitrogen atom. Based on the total mass of the positive electrode material, the mass percentage of graphitic nitrogen is C%, and 0.2≤C / B≤0.6. For example, the value of the ratio of the mass percentage of graphitic nitrogen in the carbon coating layer to the mass percentage of nitrogen in the carbon coating layer can be 0.2, 0.3, 0.4, 0.5, 0.6 or a value within the range composed of any two of these values. When the nitrogen element in the carbon coating layer on the surface of the positive electrode material exists in the form of pyridinic nitrogen, amino nitrogen, pyrrolic nitrogen, graphitic nitrogen or oxidized nitrogen, the rate discharge performance of the secondary battery can be further improved, while taking into account the improvement of the cycle performance.
[0021] In some embodiments, the chemical formula of the positive electrode material is LiMn a Fe 1-a PO 4X. 0≤a≤1. For example, the value of a can be 0, 0.1, 0.2, 0.4, 0.6, 0.9, 1 or a value in the range of any two of these values. In some embodiments, the positive electrode material also includes an X element, and the X element includes at least one of magnesium, vanadium, titanium, niobium, tungsten, molybdenum, nickel or cobalt. In some embodiments, the X element includes at least one of magnesium, vanadium, titanium or tungsten. Based on the total mass of the positive electrode material, the mass content of the X element is x ppm, 500≤x≤5000, preferably 2000≤x≤3500. For example, the mass content of the X element in the positive electrode material can be 500, 628, 1857, 2000, 3085, 3500, 3509, 4119, 5000 or a value in the range of any two of these values. In some embodiments, 5000≤x / a≤15000. The ratio of x / a can be 5000, 5073, 6978, 8864, 9682, 11406, 13348, 15000 or a value in the range formed by any two of these values. Adding the above elements to the lithium phosphate positive electrode material, and the mass content relationship meets the above range, can further improve the rate discharge performance of the secondary battery and improve the cycle performance.
[0022] In some embodiments, the D / G peak ratio of the carbon coating layer is N, 0.90≤N≤1.2. For example, the D / G peak ratio of the carbon coating layer can be 0.90, 0.92, 0.96, 1.02, 1.04, 1.10, 1.12, 1.2 or a value within the range of any two of these values. The thickness of the carbon coating layer is H nm, 1≤H≤10. For example, the thickness of the carbon coating layer can be 1, 2, 4, 5, 7, 8, 10 or a value within the range of any two of these values. The D / G value of the carbon coating layer on the surface of the lithium phosphate material is within the above range, or the thickness of the carbon coating layer is within the above range, which can improve the rate discharge performance of the secondary battery while improving the cycle performance.
[0023] In some embodiments, the diameter of the positive electrode material is D nm, 50≤D≤500. For example, the diameter of the positive electrode material can be 50, 113, 170, 198, 293, 341, 379, 476, 500 or a value in the range of any two of these values. The specific surface area of the positive electrode material is S m 2 / g, 10≤S≤50. For example, the specific surface area of the positive electrode material can be 10, 16, 20, 24, 33, 38, 42, 50 or a value in the range formed by any two of these values. The diameter of the lithium phosphate salt material is within the above range, or the specific surface area is within the above range, which can improve the rate discharge performance of the secondary battery while improving the cycle performance.
[0024] In some embodiments, the method for preparing the positive electrode material comprises the following steps:
[0025] (1) weighing a transition metal source (phosphate, oxide, carbonate, oxalate), a phosphorus source, and a lithium source in a molar ratio of transition metal: phosphorus: lithium = 1:1: (1 to 1.03), adding a nitrogen-containing carbon source in a mass ratio of 5% to 8% of the total mass of the synthesized positive electrode material, and adding a solvent to perform a first grinding treatment to obtain a first grinding slurry;
[0026] (2) drying the first polishing slurry, and then performing a first calcination treatment, calcining at 500° C. to 600° C. for 4 h to 8 h in a nitrogen atmosphere to obtain a pre-calcined material;
[0027] (3) adding a nitrogen-containing carbon source accounting for 5% to 15% of the total mass of the synthesized positive electrode material to the pre-sintered material for a second grinding and mixing process to obtain a second grinding material;
[0028] (4) The second ground material is dried and then subjected to a second calcination treatment, calcining at 700° C. to 800° C. for 5 h to 10 h in a nitrogen atmosphere to obtain a positive electrode material.
[0029] In some embodiments, the positive electrode material layer includes a positive electrode conductive material. There is no limitation on the type of positive electrode conductive material, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials may be used alone or in any combination.
[0030] In some embodiments, the positive electrode material layer includes a positive electrode binder. The type of the positive electrode binder is not particularly limited, and in the case of a coating method, any material that can be dissolved or dispersed in a liquid medium used in electrode manufacturing can be used. Examples of positive electrode binders may include, but are not limited to, one or more of the following: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, etc.; rubber polymers such as styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, etc.; thermoplastic elastomer polymers such as styrene-butadiene-styrene block copolymer or its hydride, ethylene-propylene-diene terpolymer, styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer or its hydride; soft resin polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, propylene-α-olefin copolymer; fluorine polymers such as polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, polytetrafluoroethylene-ethylene copolymer; polymer compositions having ion conductivity of alkali metal ions, etc. The above positive electrode binders may be used alone or in any combination.
[0031] There is no restriction on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder and the thickener used as needed. Examples of solvents used to form positive electrode slurries may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, mixed media of alcohol and water or water, etc. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran; amides such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; non-protonic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.
[0032] Thickeners are usually used to adjust the viscosity of the slurry. In the case of using an aqueous medium, a thickener and a styrene-butadiene rubber emulsion can be used to slurry. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners may be used alone or in any combination.
[0033] There is no particular limitation on the type of positive electrode current collector, which can be any known material suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.
[0034] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode material layer, the surface of the positive electrode current collector may include a conductive additive or a conductive coating. Examples of conductive additives may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. Examples of conductive coatings may include a mixture layer containing an inorganic oxide, a conductive agent, and a binder.
[0035] negative electrode
[0036] The negative electrode comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer comprises a negative electrode active material. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to reduce the precipitation of lithium metal on the negative electrode during charging.
[0037] The negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), silicon, silicon-carbon composites, SiO w (0.5<w<1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO 2 , spinel structure lithium titanate Li 4 Ti 5 O 12 , Li-Al alloy or metallic lithium, etc. Optionally, the negative electrode active material may further include an amorphous carbon material, and the amorphous carbon may be soft carbon (low temperature calcined carbon), hard carbon, mesophase pitch carbide or calcined coke, etc.
[0038] The negative electrode material layer also includes a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The present application does not particularly limit the type of negative electrode binder, as long as it is a material that is stable to the solvent used in the manufacture of the electrolyte or electrode. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.
[0039] The negative electrode material layer also includes a conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent can be at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots or graphene, and the above-mentioned carbon nanotubes can include but are not limited to at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes.
[0040] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide). In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 12μm, and the thickness of the single-sided negative electrode material layer is 30μm to 160μm. In the present application, the negative electrode mixture layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. This application has no special restrictions as long as the purpose of this application can be achieved.
[0041] The present application has no particular restrictions on the compaction density of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the compaction density of the negative electrode sheet can be 1.0 g / cm 3 Up to 1.85g / cm 3 The present application has no particular limitation on the cold pressing pressure of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the cold pressing pressure of the negative electrode sheet can be 3 tons to 30 tons.
[0042] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the thickness of the conductive layer, as long as the purpose of the present application can be achieved, for example, the thickness of the conductive layer is 1μm to 10μm.
[0043] Electrolyte
[0044] The electrolyte used in the secondary battery of the present application includes a lithium salt and a non-aqueous solvent that dissolves the lithium salt.
[0045] The present application has no particular limitation on the type of lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium difluorophosphate (LiPO 2 F 2 ), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalatoborate) (LiBOB) or lithium difluorooxalatoborate (LiDFOB). Based on the mass of the electrolyte, the mass percentage of the lithium salt can be 8% to 15%, for example, the mass percentage of the lithium salt can be 8%, 9%, 10%, 11%, 12.5%, 13%, 15% or a range consisting of any two of these values.
[0046] The present application has no particular restrictions on the types of the above-mentioned non-aqueous solvents, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of chain carbonate compounds or cyclic carbonate compounds. The above-mentioned chain carbonate compounds may include but are not limited to at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate or methyl ethyl carbonate. The above-mentioned cyclic carbonate compounds may include but are not limited to at least one of ethylene carbonate, propylene carbonate, butylene carbonate or ethylene ethylene carbonate. The above-mentioned carboxylate compounds may include but are not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of ethylene glycol dimethyl ether, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.
[0047] Diaphragm
[0048] In the present application, a diaphragm is usually provided between the positive electrode and the negative electrode. The diaphragm is used to separate the positive electrode plate and the negative electrode plate, reduce the problem of internal short circuit of the secondary battery, allow electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process.
[0049] The present application has no particular restrictions on the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of the separator may include at least one of woven membrane, non-woven membrane, microporous membrane, composite membrane, rolled membrane or spun membrane.
[0050] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, for example, it may be at least one of the aforementioned binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).
[0051] The pore size of the diaphragm in the present application is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In some embodiments, the thickness of the diaphragm is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the diaphragm is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the diaphragm is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the secondary battery can be ensured.
[0052] The present application also provides an electronic device, which includes the secondary battery of the present application. The electronic device includes but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini CD, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0053] Example
[0054] Hereinafter, taking lithium-ion batteries as an example, examples and comparative examples are given to more specifically describe the implementation of the secondary battery of the present application. Those skilled in the art will understand that the preparation method described in the present application is only an example, and any other suitable preparation method is within the scope of the present application. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0055] Example 1-1
[0056] 1. Preparation of positive electrode
[0057] <Preparation of positive electrode active material>
[0058] (1) Weighing iron phosphate and a lithium source at a molar ratio of transition metal: lithium = 1: (1 to 1.03), adding polyacrylamide in an amount of 5% of the total mass of the synthesized positive electrode material, and adding deionized water to perform a first grinding treatment to obtain a first grinding slurry;
[0059] (2) drying the first polishing slurry, and then performing a first calcination treatment, calcining at 600° C. for 8 h in a nitrogen atmosphere to obtain a pre-calcined material;
[0060] (3) adding a nitrogen-containing carbon source accounting for 15% of the total mass of the synthesized positive electrode material to the pre-sintered material for a second grinding and mixing process to obtain a second grinding material;
[0061] (4) Drying the second ground material and then performing a second calcination treatment at 800° C. for 8 h in a nitrogen atmosphere to obtain a positive electrode active material LiFePO 4 .
[0062] <Preparation of positive electrode sheet>
[0063] The positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) obtained in the above steps are mixed in a mass ratio of 95:2:3, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9μm, and dried to obtain a positive electrode sheet coated with a positive electrode mixture layer on one side. Repeat the above steps on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a positive electrode mixture layer on both sides. By adjusting the pressure of the cold pressing, positive electrode sheets with different compaction densities and surface roughness can be obtained. After cold pressing, striping, and welding of the pole ears, a positive electrode sheet with a specification of 74mm×867mm is obtained by drying.
[0064] 2. Preparation of electrolyte
[0065] In a dry argon atmosphere glove box, diethyl carbonate was used as the base solvent, and lithium hexafluorophosphate (LiPF 6 ) is dissolved in the above-mentioned base solvent, and vinylene carbonate is added as an additive to obtain an electrolyte. Wherein, based on the total mass of the electrolyte, LiPF 6 The mass percentage of tantalum is 12.5%, and the mass percentage of vinylene carbonate is 2%.
[0066] 3. Preparation of negative electrode
[0067] Artificial graphite is used as the negative electrode active material. The negative electrode active material, styrene-butadiene rubber (SBR), polyacrylic acid (PAA), carbon nanotubes (CNT), and carboxymethyl cellulose (CMC) are mixed in a mass ratio of 95.8:2.4:0.5:0.5:0.8, and then deionized water is added as a solvent and stirred evenly to prepare a negative electrode slurry with a solid content of 45wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried to obtain a negative electrode sheet coated with a negative electrode mixture layer on one side. Repeat the above steps on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a negative electrode mixture layer on both sides. By adjusting the pressure of the cold pressing, negative electrode sheets with different compaction densities and surface roughness can be obtained. After cold pressing, striping, and welding of the pole ears, the negative electrode sheet with a specification of 76.6mm×875mm is obtained by drying.
[0068] 4. Preparation of diaphragm
[0069] A porous polyethylene film with a thickness of 15 μm was used as the separator.
[0070] 5. Preparation of lithium-ion batteries
[0071] The positive electrode sheet, negative electrode sheet and separator are stacked in order, the separator is placed between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and the electrode assembly is wound. The electrode assembly is placed in a packaging bag, and after dehydration at 80°C, the above electrolyte is injected and packaged. After the process of formation and hot pressing (formation at 80°C / 1~2.5Mpa, time 0.5h to 2h), degassing, trimming, capacity testing and other processes, a lithium-ion battery is obtained.
[0072] 6. Test methods
[0073] (1) Carbon content test
[0074] Take a lithium-ion battery, scrape off the positive electrode material on the positive electrode sheet, put the scraped positive electrode material into the crucible of the analyzer, and heat it in a high-frequency induction furnace to promote the reaction of carbon element with oxygen to generate carbon dioxide (CO 2 ). The generated CO 2 The gas passes through the infrared detection cell and the CO is measured using the infrared absorption principle. 2 Gas concentration, calculate the carbon content concentration in the positive electrode mixture layer. Test instrument: high frequency infrared carbon and sulfur analyzer. Model: Shanghai Dekai DK-666.
[0075] (2) Nitrogen content test
[0076] For the initial positive electrode active material, a mixed solvent is used to dissolve the positive electrode material (for example, 0.4 g of the material is dissolved in a mixed solvent of 10 ml of aqua regia (nitric acid and hydrochloric acid mixed in a ratio of 1:1) and 2 ml of HF), the volume is fixed to 100 mL, and then the mass percentage of each metal element and nitrogen element in the solution is tested using an ICP analyzer;
[0077] For the positive electrode, take a lithium-ion battery, dissolve the positive electrode using a mixed solvent (for example, 0.4 g of the positive electrode uses a mixed solvent of 5 ml of aqua regia and 5 ml of deionized water), dilute to 100 mL, and then use an ICP analyzer to test the mass percentage of each metal element and nitrogen element in the solution.
[0078] (3) Nitrogen form test
[0079] For the initial positive electrode material, the material sample is measured for photoelectron spectroscopy using an XPS instrument in a vacuum environment to obtain the photoelectron peak spectrum of the nitrogen element (N1s); for the positive electrode sheet, a lithium-ion battery is taken, the positive electrode sheet is removed and cut along the thickness direction, and the material sample in the positive electrode sheet is measured for photoelectron spectroscopy using an XPS instrument in a vacuum environment to obtain the photoelectron peak spectrum of the nitrogen element (N1s). The nitrogen element is distinguished by the difference in XPS binding energy: pyridinic nitrogen (Npyri, binding energy greater than or equal to 398eV, less than 399eV), amino nitrogen (Namine, binding energy greater than or equal to 399eV, less than 400eV), pyrrolic nitrogen (Npyrro, binding energy greater than or equal to 400eV, less than 401eV), graphitic nitrogen (Ngrap, binding energy greater than or equal to 401eV, less than 402eV) and nitrogen oxide (Noxide, binding energy greater than or equal to 402eV, less than 405eV).
[0080] (4) 4C rate discharge test
[0081] Take a lithium-ion battery, charge it to 4.3V at a constant current of 0.2C rate at 25℃, then charge it at a constant voltage until the current is less than or equal to 0.05C, then let it stand for 30 minutes, and then discharge it to 2.5V at a constant current of 0.2C rate, and test to obtain the lithium-ion battery 25℃ 0.2C rate discharge capacity; at 25℃, charge the lithium-ion battery to 4.3V at a constant current of 0.2C rate, and then charge it at a constant voltage until the current is less than or equal to 0.05C; then let the battery cell stand for 60 minutes, and then discharge it to 2.5V at a constant current of 4C rate, and test to obtain the lithium-ion battery 25℃ 4C rate discharge capacity.
[0082] 4C rate discharge capacity retention rate % = 4C rate discharge capacity / 0.2C rate discharge capacity × 100%.
[0083] (5) Low temperature cycle performance test
[0084] Take the lithium-ion battery and place it in a 0℃ constant temperature test box for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it to 4.5V at a constant current of 0.5C, then charge it to a current of 0.025C at a constant voltage of 4.5V, let it stand for 5 minutes, and discharge it to 3.0V at a constant current of 0.5C. Record it as the initial discharge capacity C 0 Repeat this step for 100 cycles and record the discharge capacity C after 100 cycles. 1 , calculate the cycle capacity retention rate of lithium-ion batteries.
[0085] Low temperature cycle capacity retention rate % = C 1 / C 0 ×100%.
[0086] (6) Normal temperature cycle performance test
[0087] Take the lithium-ion battery and place it in a 25℃ constant temperature test box for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it to 4.5V at a constant current of 0.5C, then charge it to a current of 0.025C at a constant voltage of 4.5V, let it stand for 5 minutes, and discharge it to 3.0V at a constant current of 0.5C. Record it as the initial discharge capacity C 0 Repeat this step for 100 cycles and record the discharge capacity C after 100 cycles. 1 , calculate the cycle capacity retention rate of lithium-ion batteries.
[0088] Normal temperature cycle capacity retention rate % = C 1 / C 0 ×100%.
[0089] (7) High temperature cycle performance test
[0090] Take a lithium-ion battery and first charge and discharge it for the first time in an environment of 45°C. First, use a constant current charge of 0.5C to charge to 4.35V, then perform constant voltage charge, and then perform constant current discharge at a current of 0.5C to discharge to 2.8V, and record the discharge capacity of the third cycle; then perform 100 charge and discharge cycles, and record the discharge capacity of the 100th cycle.
[0091] High temperature cycle capacity retention rate %=(discharge capacity at the 100th cycle / discharge capacity at the 3rd cycle)×100%.
[0092] The lithium-ion batteries of the following embodiments or comparative examples differ from those of embodiment 1-1 only in that the mass percentages of carbon and nitrogen on the surface of the positive electrode material and the proportion of graphite nitrogen in the nitrogen element are adjusted according to Table 1. The proportions of different types of nitrogen atoms in the carbon coating layer are controlled by adjusting the type of nitrogen-containing carbon source and the sintering program parameters. The performance test results of the lithium-ion batteries of the embodiments and comparative examples are shown in Table 1 below.
[0093] Table 1
[0094]
[0095]
[0096] *In the above table, the calculation results of C / B are rounded to two decimal places.
[0097] As can be seen from Table 1, the lithium-ion battery prepared in the embodiment of the present application, when the mass percentage of carbon element in the positive electrode material satisfies 0.8≤A≤3, and the mass percentage of nitrogen element satisfies 0.2≤B≤0.8, can improve the rate discharge performance of the secondary battery, while taking into account the improvement of the cycle performance. In particular, when 1.2≤A≤2.6, or 0.3≤B≤0.5 is satisfied, the rate discharge performance of the secondary battery can be further improved, while taking into account the improvement of the cycle performance. In particular, when the mass percentage of graphite nitrogen in the positive electrode material satisfies 0.2≤C / B≤0.6, the rate discharge performance of the secondary battery can be further improved, while taking into account the improvement of low temperature, room temperature and high temperature cycle performance.
[0098] The lithium ion batteries of the following Examples 2-1 to 2-17 differ from those of Examples 1-19 only in that the ratio of manganese to iron in the positive electrode material, and the type and content of the doped metal element are adjusted according to Table 2. The elemental composition of the positive electrode material in different examples is adjusted by adjusting the type and content of the transition metal source in the initial charging step of the preparation process.
[0099] The performance test results of the lithium-ion batteries of various embodiments are shown in Table 2 below.
[0100] Table 2
[0101]
[0102]
[0103] As shown in Table 2, the lithium-ion battery prepared in the embodiment of the present application has a a Fe 1-a PO 4 When the a value in satisfies 0≤a≤1, the rate discharge performance of the secondary battery can be improved, while improving the low-temperature, room-temperature and high-temperature cycle performance. When the positive electrode material further includes magnesium, vanadium, titanium, niobium, tungsten, molybdenum, nickel or cobalt, especially magnesium, vanadium, titanium or tungsten, the rate discharge performance of the secondary battery can be further improved, while improving the low-temperature, room-temperature and high-temperature cycle performance. When the mass content of the X element satisfies 500≤x≤5000, especially 2000≤x≤3500, the rate discharge performance of the secondary battery can be further improved, while improving the low-temperature, room-temperature and high-temperature cycle performance. When 5000≤x / a≤15000, the rate discharge performance of the secondary battery can be further improved, while improving the low-temperature, room-temperature and high-temperature cycle performance.
[0104] The lithium-ion batteries of the following Examples 3-1 to 3-16 differ from those of Examples 2-14 only in that the ratio of the D / G peak of the carbon coating layer, the thickness of the carbon coating layer and the specific surface area of the positive electrode material are adjusted according to Table 3, and the diameter of the positive electrode material is screened. The ratio of the D / G peak of the carbon coating layer is controlled by adjusting the type of the nitrogen-containing carbon source and the sintering program parameters; the thickness of the carbon coating layer is controlled by adjusting the quality of the nitrogen-containing carbon source added to the pre-sintered material under the condition of controlling the total amount of the nitrogen-containing carbon source added to be equal; and the specific surface area of the positive electrode material is controlled by adjusting the amount of the nitrogen-containing carbon source and the sintering program parameters.
[0105] Table 3
[0106]
[0107]
[0108] It can be seen from Table 3 that the lithium-ion battery prepared in the embodiment of the present application, when the ratio of the D / G peak of the carbon coating layer is adjusted to meet 0.90≤N≤1.2, the rate discharge performance of the secondary battery can be further improved, while improving the low-temperature, room temperature and high-temperature cycle performance. When the thickness of the carbon coating layer is adjusted to meet 1≤H≤10, the rate discharge performance of the secondary battery can be further improved, while improving the low-temperature, room temperature and high-temperature cycle performance. When the positive electrode material is adjusted to meet 50≤D≤500, the rate discharge performance of the secondary battery can be further improved, while improving the low-temperature, room temperature and high-temperature cycle performance. When the specific surface area of the positive electrode material is adjusted to meet 10≤S≤50, the rate discharge performance of the secondary battery can be further improved, while improving the low-temperature, room temperature and high-temperature cycle performance.
[0109] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A positive electrode material, characterized in that: It comprises a core and a carbon coating layer, wherein the carbon coating layer covers at least a portion of the surface of the core; The core includes lithium phosphate, and the carbon coating layer includes nitrogen; Based on the total mass of the positive electrode material, the mass percentage of carbon element is A%, 0.8≤A≤3; Based on the total mass of the positive electrode material, the mass percentage of nitrogen element is B%, and 0.2≤B≤0.
8.
2. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following conditions: (1)1.2≤A≤2.6; (2)0.3≤B≤0.5。 3. The positive electrode material according to claim 1 or 2, characterized in that The form of the nitrogen element in the carbon coating layer includes at least one of pyridinic nitrogen, amino nitrogen, pyrrolic nitrogen, graphitic nitrogen or oxidized nitrogen; Based on the total mass of the positive electrode material, the mass percentage of the graphite nitrogen is C%, and 0.2≤C / B≤0.
6.
4. The positive electrode material according to claim 1 or 2, characterized in that The positive electrode material is LiMn a Fe 1-a PO4, 0≤a≤1.
5. The positive electrode material according to claim 4, characterized in that The positive electrode material further includes an X element, and the X element includes at least one of magnesium, vanadium, titanium, niobium, tungsten, molybdenum, nickel or cobalt; Based on the total mass of the positive electrode material, the mass content of the X element is x ppm, 500≤x≤5000.
6. The positive electrode material according to claim 5, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) The X element includes at least one of magnesium, vanadium, titanium or tungsten; (2)2000≤x≤3500; (3)5000≤x / a≤15000.
7. The positive electrode material according to claim 1 or 2, characterized in that: The D / G peak ratio of the carbon coating layer is N, 0.90≤N≤1.2; and / or, The thickness of the carbon coating layer is H nm, 1≤H≤10.
8. The positive electrode material according to claim 1 or 2, characterized in that: The diameter of the positive electrode material is D nm, 50≤D≤500; and / or, The specific surface area of the positive electrode material is Sm 2 / g, 10≤S≤50.
9. A secondary battery, characterized in that: A positive electrode sheet is included, wherein the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector; The positive electrode material layer comprises the positive electrode material according to any one of claims 1 to 8.
10. An electronic device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.
Citation Information
Cited By
Positive electrode material and preparation method thereof, positive plate and secondary battery
CN122051223A
Positive electrode material, secondary battery, and electronic device
WO2026158004A1